Green Marketing Strategies of Restaurants in Zamboanga City, Philippines - San Juan, Dolores (JPAIR Multidisciplinary Research, 2017)
As a growing awareness on the repercussion of global warming, non-biodegradable solid waste, harmful impact of the pollutants and the like, both marketers and consumers are shifting into green products and services (Eriksson, 2004). In this light, the objectives of this study are to (1) identify the green strategies of restaurants in Zamboanga City; (2) examine the reasons and benefits of adopting green strategies; and (3) investigate the challenges faced by the restaurant owners/managers in implementing green strategies. Descriptive research design was employed in the study. A survey questionnaire and an interview guide were utilized to gather data. Among the highlights of the results, the study found out that as to the green strategies, restaurant managers/owners make use of cleansers or soaps that do not harm the environment in the food establishment. Corporate social responsibility is the chief reason for adopting green strategies. Restaurant managers or owners believed that they have managerial obligation to take action to protect and improve the welfare of the society and the interest of the organization. Regarding the benefits, green strategies helps the restaurant obtain a green reputation and brand image. Lastly, pertaining to the challenges, restaurant managers/owners hold that green strategies require technology, which requires investment in research and development.
Keywords: Marketing; green strategies; descriptive design; Philippines